Answer:
The correct answer is b) 3p = 6
Explanation:
First, we need to find p:
3p - 2 = 6p + 4
-2 = 3p + 4
-6 = 3p
-2 = p
Now, we just need to plug p's value into each question:
a) 3p = 6p + 6
3(-2) = 6(-2) + 6
-6 = -12 + 6
-6 = -6
Since -6 = -6, a is not the correct answer.
b) 3p = 6
3(-2) = 6
-6 = 6
Since -6 ≠ 6, b is the correct answer.
c) -6 = 3p
-6 = 3(-2)
-6 = -6
Since -6 = -6, c is not the correct answer.
d) -3p - 2 = 4
-3(-2) - 2 = 4
6 - 2 = 4
4 = 4
Since 4 = 4, d is not the correct answer.
Therefore, b is the correct answer.